STRATEGI KOMUNIKASI POLITIK PARTAI DALAM MENGHIMPUN ASPIRASI MASYARAKAT - Jayanegara, Kms. Umar; Putri, Intan; Fardiansyah, Riko; Srimudin, Agus; Novasriandy; Hikmawati, Mutiara (Berajah Journal, 2026)
The development of digital technology has brought significant changes to political communication practices, particularly in the way political parties interact with the public. Social media is no longer used solely as a channel for disseminating information but has also become a dialogical space for collecting public aspirations in a more participatory manner. In the context of South Sumatra, complex social conditions and relatively low levels of political participation require political parties to implement communication strategies that are more inclusive and responsive. This study aims to analyze the political communication strategies employed by the South Sumatra Regional Executive Board (DPD) of the Golkar Party in gathering public aspirations. This study adopts a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, observation, and documentation studies. Informants were selected using purposive sampling and included core party officials, communication teams or social media administrators, as well as community representatives who had interacted with the party’s communication programs. Data analysis was conducted descriptively by applying source and method triangulation to ensure data validity.The findings indicate that the South Sumatra DPD of the Golkar Party implements political communication strategies through the use of social media, the organization of face-to-face dialogue forums, and community-oriented social activities. These strategies contribute to building two-way communication, strengthening relationships with the public, and serving as effective mechanisms for collecting public aspirations. However, the study also identifies challenges related to limited public media literacy and the need to enhance the communication capacities of party officials. The study concludes that inclusive, dialogical, and locally adaptive political communication strategies can improve the effectiveness of public aspiration collection and strengthen the representative function of political parties at the regional level.